2021
DOI: 10.3389/fcell.2021.771931
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in Podocyte Loss: Death or Detachment?

Abstract: Glomerular podocytes are characterized by terminally differentiated epithelial cells with limited proliferating ability; thus, podocyte loss could not be fully compensated by podocyte regeneration. A large body of clinical studies collectively demonstrated that podocyte loss correlated with glomerular diseases progression. Both podocyte death and podocyte detachment lead to podocyte loss; however, which one is the main cause remains controversial. Up to date, multiple mechanisms are involved in podocyte death,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…This would be consistent with the clinical observation that in progressive glomerular diseases, injured podocytes are lost from the glomerular capillary tuft, into the urinary space. 21 …”
Section: Resultsmentioning
confidence: 99%
“…This would be consistent with the clinical observation that in progressive glomerular diseases, injured podocytes are lost from the glomerular capillary tuft, into the urinary space. 21 …”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis of podocytes has been demonstrated in cell culture studies using various conventional techniques, while apoptosis in vivo has been reported in rodent models, mainly based on tissue staining with terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) or caspase-3 staining. Interestingly, apoptosis has not been observed in human podocytes by electron microscopy (Kriz et al, 2013;Nagata, 2016;Yin et al, 2021). These discrepant results between rodents and humans may be in part related to experimental techniques, or may represent species differences.…”
Section: The Podocyte In Health and Diseasementioning
confidence: 99%
“…Indeed, impaired autophagy causes podocyte loss [ 125 ]. For instance, deleting Atg5 gene in podocytes leads to glomerular lesions that are concomitant with podocyte loss and albuminuria [ 126 ].…”
Section: Autophagy In Diabetic Nephropathymentioning
confidence: 99%